The Efficacy and Safety of Ischemic Stroke Therapies: An Umbrella Review - Li, Yongbiao; Cui, Ruyi; Fan, Fangcheng; Lu, Yangyang; Ai, Yangwen; Liu, Hua; Liu, Shaobao; Du, Yang; Qin, Zhiping; Sun, Wenjing; Yu, Qianqian; Liu, Qingshan; et al. (Frontiers in Pharmacology, 2022)
Background: Ischemic stroke is a leading cause of morbidity and mortality. There are constantly emerging new studies of frequently employed treatments for ischemic stroke, and some results are conflicting. Therefore, it is necessary to summarize and analyze the latest published clinical research data. Objective: We aimed to perform an updated umbrella review to evaluate further the efficacy and safety of frequently employed treatments for ischemic stroke patients. Methods: We conducted a search for meta-analyses and systematic reviews on Embase, PubMed, the Cochrane Library, and Web of Science to address this knowledge gap. We examined global neurological deficit, neurological function deficit and cognitive function scores, quality of life, and activities of daily living as efficacy endpoints, and the incidence of adverse events as safety profiles. Results: Sixteen eligible papers, including 374 studies, were included in the umbrella review. The results showed that thrombolytic therapy (human urinary kallidinogenase, alteplase, tenecteplase, desmoteplase), antiplatelet agents (aspirin, clopidogrel, tirofiban), statins, heparin, MSCs, edaravone and blood-activating and stasis-dispelling herbs (NaoShuanTong capsule, Ginkgo biloba, Dengzhan Shengmai, Xuesaitong injection, Muoluoning) demonstrated undeniable positive effects in clinical effective rate, and in NIHSS, mRS, BI and neurological deficit scores. Furthermore, ischemic stroke agents were found likely to have an important effect on increasing neurological function or activities of daily living in mild to moderate ischemic stroke patients. Conclusion: Our study demonstrated that irrespective of age, gender or stroke severity, and despite an increased risk of fatal intracranial hemorrhage during the first few days after treatment, alteplase, tenecteplase, desmoteplase, antiplatelet clopidogrel, statins, heparin, NaoShuanTong capsule and Ginkgo biloba significantly improves the overall odds of a good stroke outcome when delivered within acute ischemic stroke onset. Based on conventional therapy, adding the Dengzhan Shengmai capsule, MSCs, Xuesaitong injection, edaravone and Muoluoning could reduce the mortality, recurrence rate, neurological functional deficit scores, and improve clinical effect and quality of life. Furthermore, this has few adverse reactions and a high level of safety in clinical application.